PENGARUH TINGKAT INFLASI, SUKU BUNGA DAN NILAI KURS TERHADAP HARGA SAHAM PT AGUNG PODOMORO LAND TBK - Dini Rusqiati; Adrianus Kangtono (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This research aimed to examine the independent variables which consist of, inflation rates, interest rates, and exchange rates affect the dependent variable, stock price of PT Agung Podomoro Land Tbk, both simultaneously and partially. The research was conducted by using the data from January 2012 to August 2015. This study used SPSS 22. The tests were using multiple linear regressions through the stages of classical assumption test simultaneous test F and partial T. The results showed that simultaneously the inflation rates, interest rates, and exchange rates significantly affect the stock price of PT Agung Podomoro Land Tbk. While partially, the inflation rates negatively and significantly affect the stock price of PT Agung Podomoro Land Tbk. The interest rates negatively and significantly affect the stock price of PT Agung Podomoro Land Tbk. While the exchange rates positively affect the stock price of PT Agung Podomoro Land Tbk.